Production and characterization of monoclonal antibodies to polyomavirus major capsid protein VP1. - Marriott, S J (1985)
Four hybridoma cell lines producing monoclonal antibodies against intact polyoma virions were produced and characterized. These antibodies were selected for their ability to react with polyoma virions in an enzyme-linked immunosorbent assay. The antibodies immunoprecipitated polyoma virions and specifically recognized the major capsid protein VP1 on an immunoblot. Distinct VP1 isoelectric species were immunoprecipitated from dissociated virion capsomere preparations. Two-dimensional gel electrophoresis demonstrated antibody reactivity with specific VP1 species. Monoclonal antibodies E7 and G9 recognized capsomeres containing VP1 species D, E, and F, while monoclonal antibodies C10 and D3 recognized capsomeres containing species B and C. Two of the monoclonal antibodies, E7 and G9, were capable of neutralizing viral infection and inhibiting hemagglutination. The biological activity of the monoclonal antibodies correlated well with the biological function of the species with which they reacted.